(1R,2R)-N,N `-Bis[1-(2-pyridyl)ethylidene]cyclohexane-1,2-diamine - Salga, M.S.; Khaledi, H.; Ali, H.M.; Puteh, R. (International Union of Crystallography, 2010)
In the title compound, C(20)H(24)N(4), the cyclohexane ring adopts a chair conformation with the two imine groups linked at equatorial positions. The two halves of the molecule are related by a crystallographic twofold rotation axis. The dihedral angle between the pyridine rings is 75.73 (3)degrees.